Numerical Investigation of Pressure Fluctuation Characteristics in a Centrifugal Pump with Variable Axial Clearance - Lei Cao; Zhengwei Wang; Yexiang Xiao; Yongyao Luo (International Journal of Rotating Machinery)
Clearance flows in the sidewall gaps of centrifugal pumps are unsteady as well as main flows in the volute casing and impeller, which may cause vibration and noise, and the corresponding pressure fluctuations are related to the axial clearance size. In this paper, unsteady numerical simulations were conducted to predict the unsteady flows within the entire flow passage of a centrifugal pump operating in the design condition. Pressure fluctuation characteristics in the volute casing, impeller, and sidewall gaps were investigated with three axial clearance sizes. Results show that an axial clearance variation affects the pressure fluctuation characteristics in each flow domain by different degree. The greatest pressure fluctuation occurs at the blade pressure surface and is almost not influenced by the axial clearance variation which has a certainly effect on the pressure fluctuation characteristics around the tongue. The maximum pressure fluctuation amplitude in the sidewall gaps is larger than that in the volute casing, and different spectrum characteristics show up in the three models due to the interaction between the clearance flow and the main flow as well as the rotor-stator interaction. Therefore, clearance flow should be taken into consideration in the hydraulic design of centrifugal pumps.